Komunikasi SBAR untuk Meningkatkan Kualitas Pelaksanaan Handover oleh Perawat Pelaksana - Hidayat, Muhammad Syahid; Fadilah, Ana (PENA NURSING, 2024)
An unsystematic handover process can lead to important information not being properly conveyed, which increases the risk of medical errors and jeopardizes patient safety. The application of the SBAR (Situation, Background, Assessment, Recommendation) communication method is designed to improve the quality of nurse handover by providing a clear structure for communication. The study used a quasi-experimental method with a pre-test-post-test design without a control group. The sample consisted of 30 executive nurses at Kudus Private Hospital. Data were analyzed using paired t-test and Kolmogorov-Smirnov normality test to compare handover quality before and after applying the SBAR Communication. Results were considered significant if p < 0.05. Before using SBAR communication, 33.3% of nurses showed low handover scores, 40% were in the medium category, and only 26.7% were in the high category, with a mean score of 2.8 (SD = 0.6). After the implementation of SBAR communication, there were no more nurses with low scores, 90% of nurses were in the high category, with the mean score increasing to 4.3 (SD = 0.4). Wilcoxon statistical test results showed a value of Z = -4.467 with p < 0.05, indicating a significant improvement in handover quality after using SBAR communication. The application of the SBAR communication significantly improved the quality of nurses' handover in Kudus Private Hospital, with an average increase in score of 1.5 points. This method is effective in improving communication structure, reducing errors, and increasing patient safety.